De novo design of protein binders to stabilize monomeric TDP-43 and inhibit its pathological aggregation - Gangyu Sun; Xiang Li; Jiaojiao Hu; Tianbin Yang; Cong Liu; Zhizhi Wang; Dan Li; Wenqing Xu (Proceedings of the National Academy of Sciences, 2025)
Pathological aggregation of transactive response DNA binding protein of 43 kDa (TDP-43), primarily driven by its low-complexity domain, is closely associated with various neurodegenerative diseases, including amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD). Despite the therapeutic potential of preventing TDP-43 aggregation, no effective small molecule or biomacromolecule therapeutics have been successfully developed so far. Here, we introduce a protein design strategy that yields de novo designed proteins capable of stabilizing the key amyloidogenic region of TDP-43 in its native helical conformation with nanomolar binding affinity. The binding mechanism was further characterized by the NMR and mutagenesis study. More importantly, we demonstrated that our designed protein binders efficiently reduced TDP-43 amyloid aggregation both in vitro and in cells. Our work provides a strategy for designing protein stabilizer of the native conformation of pathological proteins for preventing its amyloid aggregation, shedding light on the development of potential therapeutic approaches for ALS, FTLD, and other protein aggregation-associated diseases.